CORRIGENDUM FOR 10.1210/en.2012-2130 (Endocrinology, 2016)
Achieving pregnancy in females with congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21OHD) is one of the major challenges in the care of adult female patients. Although females across all phenotypes of CAH due to 21OHD are generally fertile, multiple factors contribute to markedly reduced fertility rates compared with the general population. These factors include urogenital malformations, psychosexual issues and most importantly hormonal imbalances. While the prevailing perception today is that pregnancy rates among women with CAH approach those of the general population and that most women who wish to conceive eventually succeed, it was shown that even in specialized centres the latency to pregnancy is substantially prolonged irrespective of the phenotype. Herein we demonstrate how pregnancy in women with CAH can be achieved as well as how treatment during pregnancy should be monitored. The crucial step is normalization of preconception progesterone concentrations in the follicular phase. To achieve this, not only the glucocorticoid (GC) dose but also the timing of hormone replacement is crucial.